Análise estatístico de parâmetros geotécnicos do ensaio de compactação: um estudo de caso em um trecho da BR-226 Pau dos Ferros 2019. - Nogueira Neto, Antonio (Universidade Federal Rural do Semi-Árido, 2019)
In the geotechnical context, for projects to combine safe and economical solutions, knowledge of the soil and subsoil for a work is a fundamental requirement, regardless of its size. Thus, with the survey of the in situ characteristics is extremely important to know the information of that area and execute safer projects. Based on this information, this work aims to carry out the geotechnical study of the superficial soils of the city of Pau dos Ferros / RN, using as a method of analysis the compaction test. After collecting the 4 points analyzed in the field, laboratory tests were performed to determine the optimum humidity of each point and its specific maximum apparent dry weights, and to compare the values obtained through the t-student statistical distribution in order to determine the optimum humidity to find correlations between the curves found. The values found are consistent with the mean values, showing small standard deviation values for the maximum apparent dry specific weight and high for the optimum humidity, and a correlation region was found between the points analyzed in the study. Therefore, for a better understanding of the region from which the samples were taken, it is recommended to use more points to bring the data statistics closer to the sample population. Only in this way is it possible to further refine the analysis and infer more accurately.
Keywords: Caracterização geotécnica; Peso específico aparente seco; Ensaio de compactação; Solos superficiais; Geotecnia; Geotechnical characterization; Specific apparent dry weight; Compaction test; Surface soils; Geotechnics; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA